Molecular Dynamics Simulation to Study the Oil/Water Interfacial Behavior of Nanoemulsions Stabilized by Different Emulsifiers - YANG Yishuang, XIONG Housheng, XIE Xin’an, LI Pan, DU Bing, LI Lu (Shipin Kexue)
To reveal the difference in the oil/water interfacial behavior of nanoemulsions prepared separately with three emulsifiers, octenyl succinic anhydride (OSA)-modified starch, Tween-80/Span-80 (T/S80), and lecithin, this study employed a rheometer and a contact angle meter to analyze the shear rheological properties and interfacial adsorption dynamics of the emulsion systems. Furthermore, molecular dynamics simulation was utilized to delve into the underlying mechanisms of their microscopic oil/water interfacial behavior. The findings revealed that OSA exhibited the lowest interfacial tension at the oil/water interface, while T/S80 demonstrated the highest diffusion rate within the oil/water interfacial layer. This was primarily attributed to the carbon chain-based structure of T/S80, which facilitated its dispersion in water. The number of hydrogen bonds formed between the OSA-modified starch-stabilized emulsion and water molecules was the largest, approximately 1 300, indicating stronger hydrophobic effect and explaining why the emulsion droplets were the closest to a sphere in shape. OSA-modified starch and T/S80 molecules tended to form van der Waals force with water molecules. In contrast, the two carbon chains of lecithin, with glycerol as its backbone, showed a more diverse range of weak interactions because of their mutual repulsion.